Notes on the genus Chrysodema from China (Coleoptera: Buprestidae: Chrysochroinae), with one new species and one new record - Qi, Zhi-Hao; Ai, Hong-Mu; Song, Hai-Tian (Zootaxa, 2022)
The genus Chrysodema currently recorded from China contains 6 species/subspecies: C. (Chrysodema) aurostriata Saunders, 1866 from Yunnan, C. (C.) lewisii nakatai Frank & Sekerka, 2020, C. (C.) eximia berliozi Descarpentries, 1948, C. (Pseudochrysodema) dalmanni dalmanni (Mannerheim, 1837), C. (P.) dalmanni penghuensis Hattori & Ong, 2020 and C. (P.) yasumatsui Kurosawa, 1954 all from Taiwan. In this study, one new species, Chrysodema (Chrysodema) hainanensis sp. nov. from Hainan Island, China is described, illustrated, and the variation is given. The host plant Toona ciliata is new for the genus Chrysodema. The differences of the new species to its related species and subspecies are discussed and keyed. C. (C.) aurostriata from Yunnan probably belonged to C. (C.) vrabeci and still need verification. C. (C.) tonkinea Kerremans, 1909 was recorded from Guangxi (new country record). All Chrysodema species and subspecies recorded from China except C. (P.) dalmanni penghuensis and the unverified C. (C.) aurostriata were examined, and a key is given for identification.